Therapeutic Vaccines for Tuberculosis: An Overview - Bouzeyen, Rania; Javid, Babak (Frontiers in Immunology, 2022)
Tuberculosis (TB), caused by Mycobacterium tuberculosis is the world’s deadliest bacterial infection, resulting in more than 1.4 million deaths annually. The emergence of drug-resistance to first-line antibiotic therapy poses a threat to successful treatment, and novel therapeutic options are required, particularly for drug-resistant tuberculosis. One modality emerging for TB treatment is therapeutic vaccination. As opposed to preventative vaccination – the aim of which is to prevent getting infected by M. tuberculosis or developing active tuberculosis, the purpose of therapeutic vaccination is as adjunctive treatment of TB or to prevent relapse following cure. Several candidate therapeutic vaccines, using killed whole-cell mycobacteria or mycobacterial fragments are in current clinical trials. Other modes of passive immunization, including monoclonal antibodies directed against M. tuberculosis antigens are in various pre-clinical stages of development. Here, we will discuss these various therapeutics and their proposed mechanisms of action. Although the full clinical utility of therapeutic vaccination for the treatment of tuberculosis is yet to be established, they hold potential as useful adjunct therapies.